In vivo Direct Conversion of Astrocytes to Neurons Maybe a Potential Alternative Strategy for Neurodegenerative Diseases - Wang, Youcui; Zhang, Xiaoqin; Chen, Fenghua; Song, Ning; Xie, Junxia (Frontiers in Aging Neuroscience, 2021)
Partly because of extensions in lifespan, the incidence of neurodegenerative diseases is increasing, while there is no effective approach to slow or prevent neuronal degeneration. As we all know, neurons cannot self-regenerate and may not be replaced once being damaged or degenerated in human brain. Astrocytes are widely distributed in the central nervous system (CNS) and proliferate once CNS injury or neurodegeneration occur. Actually, direct reprogramming astrocytes into functional neurons has been attracting more and more attention in recent years. Human astrocytes can be successfully converted into neurons in vitro. Notably, in vivo direct reprogramming of astrocytes into functional neurons were achieved in the adult mouse and non-human primate brains. In this review, we briefly summarized in vivo direct reprogramming of astrocytes into functional neurons as regenerative strategies for CNS diseases, mainly focusing on neurodegenerative diseases such as Parkinson’s disease (PD), Alzheimer’s disease (AD), and Huntington’s disease (HD). We highlight and outline the advantages and challenges of direct neuronal reprogramming from astrocytes in vivo for future neuroregenerative medicine.